Early development of Negro and White babies. Issue 1 (January 1974) - Pollak, Margaret; Mitchell, Susan
Abstract : Seventy-five babies, 25 English, 25 West Indian, and 25 Cypriot, all born in London, were examined at 1, 3, and 9 months of age on Gesell and Sheridan scales. The age of walking alone was measured. All the babies were term normal deliveries, weighing 2500 g or more. They were examined under identical conditions. A statistically significant acceleration in gross motor function was found in the West Indian infants at 1 month, compared with the English and Cypriot infants. The acceleration related to extension. At 3 months all three groups were at the same developmental level, and at 9 months both the English and Cypriot babies were ahead of the West Indian infants in adaptive, language, and personal-social development. No significant difference in mean age of walking between the three groups was found.